Asesmen Teknologi untuk Mesin 3D Printer di Laboratorium Desain Produk dan Inovasi - Salsana, Bella; Siboro, Benedikta AH; Manik, Yosef (JST (Jurnal Sains dan Teknologi), 2022)
The purpose of this study was to identify differences performance 3D printer machine A and 3D printer machine B as the main technoware facilities in Lab. Desprin. By using comparative analysis could obtain the mapping of the most relevant 3D printer machine types for each course served by Lab. Desprin. The type of research used was experiment with the variables analyzed are production cost, dimensional precision, production time, deformation, and surface roughness. From the results of analysis the main characteristic differences were in the variables of production time, dimensional precision, and surface roughness. These results were used to map the application of 3d printer into learning needs in all coursed served by Lab Desprin.